Caracterização físico-química, microbiológica e compostos bioativos de farinhas de cascas e bagaço de kiwi (Actinidia deliciosa) e aplicação em patê - Soquetta, Marcela Bromberger (2015)
Pâté or paste is made up primarily of fats, proteins and water, being susceptible to deterioration reactions, such as lipid oxidation. Antioxidants are used to slow this processes, with the synthetic ones being more utilized, however, because they are safer, natural sources have been analyzed, like fruit residues, that are rich in phytochemicals while simultaneously provide an alternative to waste. Kiwi is a fruit know worldwide by its taste and high nutritional value. The transformation of these in flour is important do to volume reduction and perishability. The objective of this study was to determinate the bioactive compounds of flours of peel and pomace from two variations (Bruno and Monty) of kiwi (Actinidia deliciosa), unripe and ripe, and the application of the flour with the highest antioxidant activity in different concentrations in ham pâtés. To obtain the flour was used an oven at 35 ± 5 ºC, analytical mill and sieves for standardization of particle size. Analisys of chemical composition, pH determination, water activity, microbiological characterization, antimicrobial activity, determination of bioactive compounds, vitamin C, total phenolics, chlorophylls, total carotenoids, total flavonoids and antioxidant activity (DPPH and FRAP) were performed. According to the results, kiwi peel flour from the Bruno variety in the first stage of maturation was the sample with the highest antioxidant activity by the DPPH metod (72,04% of maxim activity) and with the highest level of total phenols (1262,34 mg GAE/100g), being therefore the flour chosen for elaboration of the pâtés, which followed the procedures described by Terra (1998). The ingredients were mixed in cutter for emulsification, packaging and pasteurization at 73 ºC in the interior of the mass. The formulations differ in relation to the antioxidant, them being: T1 standard, with addition of sodium erythorbate; T2 control, without antioxidant addition; T3, T4 and T5 with addition of natural antioxidant, kiwi peel flour (FCK) in different concentrations 0.5, 1.0 and 2.0%, respectively. After the product was finished, analysis of chemical composition, pH, color, lipid oxidation, DPPH, vitamin C, texture, microbiological and sensory analysis were performed. The ham pâtés were within the law requisites for chemical composition and microbiological stability, did not show oxidative changes during storage and showed good sensory acceptability for the concentrations of 0,5 and 1,0% of kiwi peel flour (FCK). The ham pâtés added with kiwi flour can be considered functional foods, having over 3 g of dietary fiber in every 100 g of pâté. Within the results was observed that the kiwi flours are characterized as an important source of bioactive compounds and dietary fiber, enabling its use as an ingredient in meat products.